PENGARUH SUHU PEMANASAN DAN KONSENTRASI CARBOPOL TERHADAP KARAKTERISTIK SABUN CAIR CUCI TANGAN - Kartika Sari, Ni Wayan Titin; Ganda Putra, G. P.; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): September, 2019)
Liquid soap is a liquid skin cleansing preparation made from basic ingredients of soap (potassium compounds with fatty acids from vegetable or animal oils). The purpose of this study was to determine the effect of heating temperature and carbopol concentration on the characteristics of hand washing liquid soap, as well as to determine the heating temperature and the best concentration of carbopol to produce hand washing liquid soap. This study used a factorial randomized block design with a 2-factor trial. The first factor is the heating temperature which consists of 3 levels are : 70?C, 80?C, 90?C. The second factor is the concentration of carbopol which consists of 3 levels are: 1%,  2%, 3%. The results showed that the heating temperature, carbopol concentration and interaction between the two treatments had a very significant effect on viscosity. Comparison of heating temperature has a very significant effect, but the concentration of carbopol and interaction between treatments has no significant effect on specific gravity and stability of foam. The ratio of carbopol concentration has a very significant effect, heating temperature has a significant effect but the interaction between the two treatments has no significant effect on the foam height. The treatment of heating temperature, carbopol concentration and interaction between treatments had no significant effect on water holding capacity, pH, free alkali and overall reception. The best treatment was obtained from the treatment of 80?C heating temperature with 1% carbopol concentration. Keywords: Heating temperature, carbopol concentration, saponification, liquid soap.